Approaches for disease prioritization and decision-making in animal health, 2000–2021: a structured scoping review - Amenu, Kebede; McIntyre, K. Marie; Moje, Nebyou; Knight-Jones, Theodore; Rushton, Jonathan; Grace, Delia (Frontiers in Veterinary Science, 2023)
This scoping review identifies and describes the methods used to prioritize diseases for resource allocation across disease control, surveillance and research, and the methods used generally in decision making on animal health policy. Three electronic databases (Medline/PubMed, Embase and CAB Abstracts) were searched covering 2000-2021. Searches identified 6395 articles after de-duplication, with an additional 64 articles added manually. A total of 6460 articles were imported to online document review management software (sysrev.com) for screening. Based on inclusion and exclusion criteria, 532 articles passed the first screening and after a second round of screening, 336 articles were recommended for full review. A total of 40 articles were removed after data extraction. Another 11 articles were added, having been obtained from cross-citation of already identified articles, providing a total of 307 articles to be considered in the scoping review. The results show that the main methods used for disease prioritization were based on economic-analysis, multi-criteria evaluation, risk assessment, simple ranking, spatial risk mapping and simulation modelling. Disease prioritization was performed to aid decision-making related to various categories: 1) disease control, prevention, or eradication strategies, 2) general organizational strategy, 3) identification of high-risk areas or populations, 4) assessment of risk of disease introduction or occurrence, 5) disease surveillance and 6) research priority setting. Of articles included in data extraction, 50.5% had a national-focus, 12.3% local, 11.9% regional, 6.5% sub-national and 3.9% global. In 15.2% of the articles, the geographic focus was not specified. The scoping review revealed the lack of comprehensive, integrated, mutually compatible approaches in disease prioritization and decision support tools for animal health. Further recommended work includes creating comprehensive and harmonized frameworks describing methods for diseases prioritization and decision-making tools in animal health.